2012
DOI: 10.1088/0256-307x/29/1/018103
|View full text |Cite
|
Sign up to set email alerts
|

The Field Emission Characteristics of Titanium-Doped Nano-Diamonds

Abstract: An electrophoresis solution, prepared in a specific ratio of titanium (Ti)-doped nano-diamond, is dispersed by ultrasound and the nano-diamond coating is then deposited on a polished Ti substrate by electrophoresis. After high-temperature vacuum annealing, the appearance of the surface and the microstructures of the coating are observed by a metallomicroscope, scanning electron microscopy and Raman spectroscopy. The field emission characteristics and luminescence features are also tested, and the mechanism of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…It was found that the electronic gap state provided by the added N is beneficial to enhance the electron field emission at the surface of ND films [ 83 ]. Many attempts/changes were conducted for improving the field emission properties, such as adjusting the grain size and boundary, the concentration of sp 2 phase, and doping type/level [ 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 ].…”
Section: Field Emission Properties Of Nd Filmmentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that the electronic gap state provided by the added N is beneficial to enhance the electron field emission at the surface of ND films [ 83 ]. Many attempts/changes were conducted for improving the field emission properties, such as adjusting the grain size and boundary, the concentration of sp 2 phase, and doping type/level [ 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 ].…”
Section: Field Emission Properties Of Nd Filmmentioning
confidence: 99%
“…Additionally, metal is another comment doping material to improve the field emission properties of ND film, which can not only effectively lower the residual stress and modify the carbon films’ mechanical property, but also simultaneously improve the capability of emitting electrons. Yang Y. et al proposed a titanium (Ti)-doped ND coating using electrophoresis and annealing (EPD @annealing) process, and studied the influence of Ti doping amount on the morphology, structure, and the field emission properties [ 92 ]. As exhibited in Figure 9 a, as the amount of Ti powder increases, the irregular grain arrays are formed and increased.…”
Section: Field Emission Properties Of Nd Filmmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9] Effective doping can modify some of these properties. [10][11][12][13][14] Attempts have been made to dope diamond films using various elements. Phosphorus, sulfur, and boron are considered as potential doping elements.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, cold cathode electron field emitters are desirable for FE displays and other vacuum microelectronic devices. [2] Since the first study of the field emission (FE) of carbon nanotubes (CNTs) in 1995 by W. A. de Heer and coworkers, [3] the FE of carbon materials such as amorphous carbon, [4] diamond, [5][6][7] carbon nanofibers, [8] graphite, [9] and carbon films [10] has gained considerable interest and been intensively investigated. Among these, CNTs [11,12] have shown excellent FE properties owing to their large aspect ratio, excellent electrical conductivity, high thermal conductivity, and good mechanical properties.…”
mentioning
confidence: 99%